KEMAMPUAN CORPORATE SOCIAL RESPONSIBILITY (CSR) MEMODERASI PENGARUH GOOD CORPORATE GOVERNANCE (GCG) DAN PROFITABILITAS PADA NILAI PERUSAHAAN - Sang Ayu Made Wiska; I Gede Cahyadi Putra; Luh Komang Merawati (Program Studi Akuntansi Fakultas Ekonomi dan Bisnis Universitas Mahasaraswati Denpasar, 2018)
Company value as an investor’s view of the company’s success rate. Good corporate governance and profitability can affect the value of the company. Beside that, corporate social responsibility strategy could provide a good corporate image to external parties and support the value of the company. This study aimed to test and obtained empirical evidence the ability of corporate social responsibility to moderate the influence of good corporate governance and profitability on company value. The population are real estate and property companies listed on Indonesia Stock Exchange in the period 2013-2015. Determination of sample using purposive sampling technique. The analysis technique used in this research is multiple linear analysis with Moderated Regression Analysis (MRA). The results showed that the variables of good corporate governance and profitability have a positive effect on company value. However, corporate social responsibility is statistically unable to moderate the influence of good corporate governance andprofitability on company value.